EFFORTS TO PREVENT HYPERTENSION IN COMMUNITY THROUGH THE USE OF HOUSEHOLD MEDICINAL PLANTS (TOGA)AT PUSKESMAS DADOK TUNGGUL HITAM, PADANG - Yuanita Ananda; Mulyanti Roberto Muliantino; Zifriyanthi Minanda Putri; Edo Gusdiansyah; Muthmainnah (Warta Pengabdian Andalas, 2025)
Hypertension is one of the non-communicable diseases whose prevalence is increasing in the community. Lifestyle factors, unhealthy diet, and lack of physical activity are the leading causes. Efforts to prevent hypertension can be made with a promotive and preventive approach, one of which is through the use of family medicinal plants (TOGA). The use of TOGA is increasingly favoured because its low side effects are more suitable for various metabolic and degenerative diseases. One area with a high incidence of hypertension is the Dadok Tunggul Hitam Community Health Centre in Padang. The high incidence of hypertension in the area is because patients suffering from hypertension who seek treatment at the health centre are not adherent to a diet and do not know the correct way of treatment. Thus, it is important to provide education about the treatment of hypertension by utilising Family Medicinal Plants in the community in the area. The implementation of the activity was carried out on 29 September 2024 by conducting a pretest first to determine the understanding of the community before being given the intervention, then continued with health checks, providing education, and handing over Family Medicinal Plants (TOGA) seeds for hypertension patients and at the end of the session a posttest was conducted again. The results showed that community knowledge before education was 65% and 100% after education. This increased because the community was enthusiastic about participating in education. The health center should monitor and evaluate the results of this education regularly.